A New Routine for Analyzing Brief Symptom Inventory Profiles in Chronic Pain Patients to Evaluate Psychological Comorbidity - Franke, Gabriele Helga; Jagla-Franke, Melanie; Küch, Dieter; Petrowski, Katja (Frontiers in Psychology, 2021)
Question: Comorbidity, i.e. the additional psychological distress in patients suffering from chronic somatic diseases (f.e. orthopedic conditions), is of growing importance. The quality of analyzing and interpreting the often-used Brief Symptom Inventory (BSI) in orthopedic patients should improve using a new “case definition”, regarding four – instead of two – groups of differentially psychologically distressed patients. Methods: The new four groups with different psychological distress: „no“, „mild“, „remarkable“, and „severe psychological distress” should be analyzed in a group of 639 orthopedic patients in inpatient rehabilitation clinics. The BSI is transformed into T values (M=50, SD=10). There is “no” distress if no T(2 scales) ≥60 and “mild” distress if T(2 scales) and/or T(GSI) ≥60 and <63. If T(2 scales) and/or T(GSI) ≥63 and <70 it is “remarkable” and if T(2 scales) and/or T(GSI) ≥70 it speaks for “severe” psychological distress. Results: The new tool for analyzing psychological distress, based on the T-scores of the BSI, resulted in the following four groups: No psychological distress (41.9%): unspecific health-related information is a useful intervention. 13.3% demonstrated low psychological distress: shorter diagnostic interviews and a few more diagnostic examinations led to low level ambulant group program to improve health and well-being in a preventive sense; one repeated measurement in four weeks is advised. Remarkable psychological distress (26%): in-depth exploration using interviews, tests and questionnaires to choose specific interventions in a single and/or group-setting, ambulant or in-patient treatment; repeated measurements and process control. 18.8% reported severe psychological distress: in-depth exploration led to specific interventions in a single and/or group-setting, almost in-patient setting; immediately crisis-intervention and high-frequent process-control. Conclusion: The new evaluation strategy of the BSI should improve practice and research; further investigation is necessary.